Position of Indonesia's Crude Palm Oil Export Market in Major Importing Countries: An Almost Ideal Demand System Approach - Dwi Nurul Amalia; Dedi Budiman Hakim; Sahara; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Although Indonesia holds the largest share of global crude palm oil (CPO) exports, large market share does not necessarily imply market power. Competition with Malaysia remains intense in major importing countries, particularly India, Pakistan, and China, where differences in demand structure and price responsiveness may shape each supplier’s export position.Purpose: This study aims to (1) analyze Indonesia’s CPO export market share in major importing countries and (2) evaluate Indonesia’s export market position relative to Malaysia using a demand-system approach.Design/methodology/approach: Monthly data for 1994–2023 were compiled from UN Comtrade, ITC, BPS, and FAOSTAT. The analysis applies the Almost Ideal Demand System (AIDS) estimated using the Seemingly Unrelated Regression (SUR) method to identify demand responses and substitution patterns between Indonesian and Malaysian CPO exports.Findings/Result:The results show that Indonesia’s CPO exports dominate the Pakistani market, maintain a strong position in India, and face balanced competition in China. Elasticity estimates indicate relatively stable demand in India and Pakistan, whereas stronger substitution patterns and higher price sensitivity characterize the Chinese market.Conclusion: Indonesia’s export position varies across markets: strongest in Pakistan, strong in India, and more competitive in China. These differences reflect heterogeneous demand structures and varying levels of substitution between Indonesian and Malaysian CPO.Originality/Value (State of the Art): This study provides a long-term market-specific assessment of Indonesia’s CPO export positioning using a theoretically consistent AIDS framework. The findings contribute new empirical evidence on substitution dynamics and competitive interactions between Indonesia and Malaysia in major global CPO markets. Keywords: AIDS, CPO, demand-system approach, export market, market position